Kadar Protein Kecap Lamtoro Dengan Variasi Volume Ekstrak Pepaya Dan Lama Waktu Hidrolisis - Pinuji, Putri Arum; , Dra. Aminah Asngad, M.Si (2015)
Ketchup is processed or preserved products are usually made from soybeans with liquid or viscous texture. The purpose of this study was to determine levels of protein and soy acceptance lamtoro with papaya extract volume variation and long hydrolysis time. Protein levels were measured as total protein using Kjehdahl. The design of this study with a completely randomized design 2 factors: factor 1: papaya extract 100 ml V1); Papaya extract 120 ml (V2); Papaya extract 140 ml (V3) and factor 2: Time Hydrolysis 1 day (W1); Hydrolysis time 3 days (W2); Hydrolysis time 5 days (W3). In this study, the hydrolysis process is done by adding papaya extract that contains the enzyme papain as a proteolytic enzyme. Papaya extract volume and time of hydrolysis affect protein levels. Results showed that the highest protein content of V3W3 (papaya extract 140 ml with hydrolysis time of 5 days) total 1,478 and the lawlest protein content of . V1W1 (papaya extract 100 ml with hydrolisis time 1 day) total 0,963. Quality soy dominant lamtoro brown, less flavorful typical, with a viscosity of less viscous, and has a less sweet flavor, while its power is less like to thank the panelists.